Use of Non-Conventional Cell Disruption Method for Extraction of Proteins from Black Yeasts - Čolnik, Maja; Primožič, Mateja; Knez, Željko; Leitgeb, Maja (Frontiers in Bioengineering and Biotechnology, 2016)
The influence of pressure and treatment time on cells disruption of different black yeasts and on activities of extracted proteins using supercritical carbon dioxide process was studied. The cells of three different black yeasts Phaeotheca triangularis, Trimatostroma salinum and Wallemia ichthyophaga were exposed to supercritical carbon dioxide (SC CO2) by varying pressure at fixed temperature (35 °C). The black yeasts cell walls were disrupted and the content of the cells was spilled into the liquid medium. The impact of SC CO2 conditions on secretion of enzymes and proteins from black yeast cells suspension was studied. The residual activity of the enzymes cellulase, β-glucosidase, α-amylase and protease was studied by enzymatic assay. The viability of black yeast cells was determined by measuring the optical density of the cell suspension at 600 nm. The total protein concentration in the suspension was determined on UV-Vis spectrophotometer at 595 nm. The release of intracellular and extracellular products from black yeast cells was achieved. Also, the observation by an environmental scanning electron microscopy shows major morphological changes with SC CO2 treated cells. The advantages of the proposed method are in a simple use which is also possible for heat sensitive materials on one hand and on the other hand integration of the extraction of enzymes and their use in biocatalytical reactions.